Efektivitas Inkubator Bisnis dalam Menciptakan Wirausaha pada Gerakan Nasional 1000 Startup Digital di Provinsi Jawa Barat - Yustika Yustika; Dede Kurnia; Ismail Yusuf (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the effectiveness of the National Movement of 1000 Digital Startups Program in West Java Province, which is part of an initiative by the Ministry of Communication and Information Technology and integrated into the MSIB Batch 6 Program. The program aims to build an inclusive, collaborative, and sustainable digital startup ecosystem through structured learning, mentoring, and guidance from experienced practitioners. This research applied a quantitative descriptive approach using a survey of 50 participants, representing the roles of Hustler, Hipster, and Hacker. Data were collected through a Likert-scale questionnaire comprising 11 learning outcome indicators. The results show an average effectiveness score of 127.9, which falls into the “high” category and exceeds the threshold for being considered effective (>117.3). Most indicators were rated high, while timeliness and target approach were rated moderate. These findings indicate that the program successfully delivers tangible benefits to participants; however, sustaining the businesses after the program remains a challenge. The implications suggest that further attention is needed on post-program support and strategies to ensure long-term business continuity for graduates.